O ensino de análise linguística e os professores em formação inicial : a relação teoria-prática - Doretto, Shirlei Aparecida (2014)
The educational scenery, mainly from the 1980s, has motivated studies and researches aiming the improvement of education. Although there are several books and researches concerning pedagogical practice in portuguese teaching, according to antunes (2003), this scenery still shows little change regarding teaching and learning processes of the discursive practices of language use, reading and writing, as well as a reflection about this use, the linguistic analysis (LA). Allied to these works, there are a number of actions promoted by the governmental institutions, in national and state range, with the development of laws, guiding documents and courses for teachers' continuing education. Actions are also accomplished at graduation level, with the development of guidelines, laws and resolutions which aim, in general lines, at guaranteeing for the teachers in initial education a greater contact with contents and pedagogical practices, overcoming the historical misconception that theory and practice are dissociable in social practice. Believing that these teachers in initial education will be, in the future, responsible for forwarding the practices of language teaching and learning in schools, we understand it is of fundamental importance to discuss aspects related to their initial education. Thus, we aim at investigating and analyzing how are built the relations between the teachers in initial education from the 4th grade of the languages course at UNESPAR/Campus of Campo Mourão, in Paraná's northwest, and the axis of reflection about language, the LA, in the discipline of teaching practice, in the preparation of pedagogical sequences, assessing the relation theory-practice. For that, we conducted a case study, through an ethnographic approach, with observation, description and analysis of data, featuring a qualitative-interpretive research. Thus, the analysis corpus consists of records collected through video and audio recordings of all the classes from the discipline of teaching practice during the first quarter 2012, semi structured interview with the discipline's teacher, works developed by students in the discipline, and written notes. Our theoretical framework is based on the assumptions of the interactionist based applied linguistics, on the theoretical and methodological assumptions of scholars who have dedicated themselves to LA, such as Antunes (2003, 2007, 2010, 2012), Geraldi (1997, 2002a, 2002b), Mendonça (2006), Perfeito (2005, 2007, 2011), Ritter (2012), Suassuna (2006, 2012), Travaglia (1996, 2011), among others. For the approach of the relation theory-practice, we sought the aid of the official guiding documents of teaching practice, such as the national curricular parameters (parâmetros curriculares nacionais - PCN), laws, guidelines and resolutions that deal with the subject. The results show that the LA relation theory-practice does not come to be an effective praxis in the analyzed group of students, because there is an attempt of promoting activities of reflection for grammatical teaching that bumps into other difficulties which indicate formation problems, not only in dealing with the language and its grammar, but also of reading and writing.